An Overview of Covid-19 Impact on Power Grid Operation in Malaysia - Ahmed Mohamed, Ahmed Haidar (FENG Bulletin, 2021)
The first notable impact of COVID-19 on the states and regions connected to the National power grid in peninsular Malaysia was a decreased ramping of load demand, particularly during usual peak demand hours. Due to the uncertainty in the transmission rates of this pandemic, the electricity demand will continue to fluctuate because of the change in human behavior and lifestyle globally.